(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
In order to determine a retrospective study data were collected from all 2031 COVID-19 patients detected by PCR (nasal swap) from January/ 2020- January /2021 for Fallujah General Teaching Hospital ,which total number of Positive covid19 were 210 in isolation ward and Negative number of COVID-19 were 1821.The study condense on bacterial co-infections and antibacterial therapy for this bacteria. Clinical information were : the genera females were 60 ( 28.5%) and were males 150 (71.4%). microbiological detected isolation from blood sample through 48hour of 210 COVID-19 patients in isolation ward detected by BACT/ALERT® Culture Media(1)then cultured on routine bacteriological media according to(2)for positive growth isolated bacteria then identification were done by biochemical test. The result of bacterial isolation from blood of patients assumptive co-infections among 210 samples, positive growth isolated of bacteria which were 121 (57,6%) and included S. pneumoniae , S. aureus , S. epidermidis, K. pneumoniae, p. aeroginosa and E. coli and total negative isolated which indeed enclose 89 (42.3%). Depending on ABS achieve guidelines, the most commonly used antibiotic way was Meropenem, Azithromycin and Cefixime with a median duration of 6 (range 1–13) days in isolation ward and when using Antibiotic Susceptibility test expressed each resistant and sensitive bacteria to antibiotic discs for all positive isolate and detected by sensitivity patterns of VITEK2 system to some species as ensuring method, but; the study focus on co-infection had the highest frequency of Staphylococcus aureus 57 (47.1%) isolates which were resistant to Ciprofloxacin, Chloramphenicol, Gentamycin, Amikacin, azithromycin, Cefotaxime, tetracycline ,Trimethoprim/ Sulphamethoxazole and sensitive to Levofloxacin and imipenem.